1984
DOI: 10.1288/00005537-198406000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Cystic metastasis from occult tonsillar primary simulating branchiogenic carcinoma: The case for tonsillectomy as a “grand biopsy.”

Abstract: The occult primary is a problem well known to head and neck surgeons. Less frequently discussed, but well documented, is cystic degeneration of metastatic nodes. When these conditions combine, they can suggest tumor arising in a pre-existing cervical cyst. This is a controversial condition, rare if it occurs at all, and is not to be invoked lightly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Literature search identified 1035 studies (Figure ); after scrutinizing titles and abstracts, 1003 were excluded as non‐relevant, concerning other diseases, duplicates, non‐original studies, or non‐English studies. Forty‐two articles, which included palatine tonsillectomy in the diagnostic approach of SCCUP, were screened in full‐text: 4 studies were from the same institution, more precisely 2 from the University of Florida College of Medicine and 1 from The Johns Hopkins Hospital, and another 1 from the University of Pittsburgh Medical Center, which subsequently published 3 updated series included in the review; 4 studies contained non‐SCC histopathology; 6 studies have not reported enough information about the negativity of the physical examination and/or conventional cross‐sectional imaging carried out before tonsillectomy; 3 studies using TLM as surgical approach to the palatine tonsil were lacking data on the state of conventional imaging before EUA or on tonsillectomies performed; 7 studies did not specify the number of tonsillectomies performed; 2 studies had suspicious findings on physical examination and/or conventional cross‐sectional imaging carried out before TORS tonsillectomy; 1 was an anatomopathological study without any clinical information on patients involved; and 1 study conducted palatine tonsillectomy before conventional imaging. Excluded studies and respective reasons of exclusion are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Literature search identified 1035 studies (Figure ); after scrutinizing titles and abstracts, 1003 were excluded as non‐relevant, concerning other diseases, duplicates, non‐original studies, or non‐English studies. Forty‐two articles, which included palatine tonsillectomy in the diagnostic approach of SCCUP, were screened in full‐text: 4 studies were from the same institution, more precisely 2 from the University of Florida College of Medicine and 1 from The Johns Hopkins Hospital, and another 1 from the University of Pittsburgh Medical Center, which subsequently published 3 updated series included in the review; 4 studies contained non‐SCC histopathology; 6 studies have not reported enough information about the negativity of the physical examination and/or conventional cross‐sectional imaging carried out before tonsillectomy; 3 studies using TLM as surgical approach to the palatine tonsil were lacking data on the state of conventional imaging before EUA or on tonsillectomies performed; 7 studies did not specify the number of tonsillectomies performed; 2 studies had suspicious findings on physical examination and/or conventional cross‐sectional imaging carried out before TORS tonsillectomy; 1 was an anatomopathological study without any clinical information on patients involved; and 1 study conducted palatine tonsillectomy before conventional imaging. Excluded studies and respective reasons of exclusion are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The extent of metastasis in terms of the number and size of positive nodes, the numerically highest level of involvement, and extent of ECS was greatest in the oropharyngeal tumours, and this has been reported previously 19,24,26 . The large size of the metastatic deposit is explained in part by the occurrence of cystic metastases which are particularly associated with tonsillar carcinoma but are seen also at other oropharyngeal sites 10,17 . The detection of ECS in 69% of metastasizing cheek tumours is surprising given the small size of the nodal deposits (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…8,9,15,48 Diagnostic tonsillectomy has been recommended to rule out clinically inapparent microinvasive tonsillar carcinoma seen with cystic metastasis in the lateral neck. 6,8,9,11,12,18,48 Previous tonsillectomy, however, does not preclude the development of a primary malignancy in the tonsillar fossa.…”
Section: Discussionmentioning
confidence: 99%